William S. Burroughs cutting up the century - Hawkins, Joan, 1953-; Wermer-Colan, Alex; Cannon, Charles; Brewer, Tony; Palmer, Landon; Harris, Oliver (Oliver C. G.) (Indiana University Press, 2019)
William S. Burroughs Cutting Up the Century is the definitive book on Burroughs' overarching cut-up project and its relevance to the American twentieth century. It features original essays, interviews, and discussions by established Burroughs scholars, respected artists, and people who encountered Burroughs. The essays consider Burroughs from a range of starting points--literary studies, media studies, popular culture, gender studies, post-colonialism, history, and geography.